The Influence of Workforce Competence and Supervision Systems on Construction Project Productivity - Rakhmawati, Annisa Nur; Khalilah Daud Isaac Makhmut; Eko Tjahjono; Ratna Marhaenita Widjaja (Universitas Kristen Cipta Wacana, 2025)
The construction industry plays a strategic role in supporting national development, but low labor productivity remains a challenge, especially in medium-scale construction projects. Labor productivity is influenced by various factors, including competence and the effectiveness of the monitoring system. Although a number of previous studies have examined these two variables, the findings show inconsistencies, so further study is needed to confirm their contribution to construction project productivity. This study aims to analyze the effect of labor competence and the monitoring system on construction project productivity. This study uses a quantitative approach with an explanatory research type. A sample of 72 respondents was determined using purposive sampling from a population of 80 workers on the PT Y boarding house construction project in Malang City. Data collection was carried out through questionnaires, observations, and documentation. Data analysis used multiple linear regression with the support of validity, reliability, and classical assumption tests. The results showed that both workforce competency and the supervision system had a significant effect on project productivity. The supervision system variable showed the most dominant effect with a significance value of 0.000 and a regression coefficient of 0.538, while workforce competency had a significance value of 0.014 with a regression coefficient of 0.412. Simultaneously, both variables have a significant effect on productivity with an R-Square value of 0.620, which means that 62% of productivity variation can be explained by these two variables.